2021
DOI: 10.3390/foods10061404
|View full text |Cite
|
Sign up to set email alerts
|

Theanine Improves High-Dose Epigallocatechin-3-Gallate-Induced Lifespan Reduction in Caenorhabditis elegans

Abstract: Epigallocatechin-3-gallate (EGCG) is the most abundant polyphenol in green tea. Our previous report showed that induced hormesis was a critical determinant for the promotion of a healthy lifespan in Caenorhabditis elegans. In the present study, we investigated the anti-aging effects of the main active ingredients in green tea. We found that galloylated catechins (EGCG and epicatechin gallate) could extend the lifespan of C. elegans, while their metabolites (gallic acid, epicatechin, and epigallocatechin) could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In the present study, serum concentrations of EGCG were only around 4 μM as indicated above, and hepatic quinoprotein levels were significantly increased but not dramatically as seen in the case of HepG2 cells treated with 400 μM EGCG . These results suggest that l -theanine can attenuate potential side effects of EGCG, being consistent with a recent report that l -theanine prevents against high-dose EGCG-induced lifespan reduction and other adverse effects in Caenorhabditis elegans …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, serum concentrations of EGCG were only around 4 μM as indicated above, and hepatic quinoprotein levels were significantly increased but not dramatically as seen in the case of HepG2 cells treated with 400 μM EGCG . These results suggest that l -theanine can attenuate potential side effects of EGCG, being consistent with a recent report that l -theanine prevents against high-dose EGCG-induced lifespan reduction and other adverse effects in Caenorhabditis elegans …”
Section: Resultssupporting
confidence: 85%
“…32 These results suggest that L-theanine can attenuate potential side effects of EGCG, being consistent with a recent report that L-theanine prevents against high-dose EGCG-induced lifespan reduction and other adverse effects in Caenorhabditis elegans. 34 3.7. L-Theanine Attenuates EGCG Hepatotoxicity.…”
Section: L-theanine Forms a Complex With Copper Andmentioning
confidence: 99%
“…This was because high-dose EGCG accelerated the biological aging process via triggering the nuclear accumulation of DAF-16 (homolog of mammalian fork head box transcription factors class O). Nonetheless, combining high-dose EGCG with theanine reversed high-dose EGCG-induced lifespan reduction in C. elegans ( Peng et al, 2021 ). Considering this current limitation, the characterization of dose-specific responses of EGCG will help us understand how EGCG targets aging-metabolic pathways while also avoiding deleterious effects on health.…”
Section: Clinical Utility and Control Of Biological Aging And Age-rel...mentioning
confidence: 99%
“…Moreover, genes in C. elegans share a great similarity (60–80%) to human genes, including many homologous genes associated with human disease [ 11 ]. As a consequence, C. elegans is thought to be an outstanding model animal for research on toxicity, due to its predictability of results in higher eukaryotes (e.g., humans and rats) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%